UTILIZATION OF OLD NUTMEG FLESH WASTE IN MALUKU - Dumadi, Suryatmi Retno (BPPT)
Until the end of 2007, nutmeg flesh had been disposed as a waste because it is not harnessed into a valuable product in nutmeg producer area on the island of Ambon and Banda in Maluku. Diversification treatment from nutmeg flesh waste into syrup can provide economical value to the product, and health benefits to those who consume it. Manufacturing process done by using simple apparatus starts from extracting nutmeg liquid, sterilizing nutmeg syrup container, mixing with sugar, bottling, labeling to produce salable nutmeg syrup. The 1:1 ratio of nutmeg liquid to sugar gives good taste and preferred. Extracted flesh waste has been utilized as nutmeg flesh cake by mixing sugar in ratio of 1:1, battering evenly and drying in the sun or a heating oven at temperature of 50 oC to produce tasty nutmeg cake with economical value-added.keywords : nutmeg flesh waste, nutmeg syrup, old nutmeg.